2014
DOI: 10.3846/20294913.2014.979456
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Corporate Financial Performance Using Sentiment in Annual Reports for Stakeholders’ Decision-Making

Abstract: This paper is aimed at examining the role of annual reports’ sentiment in forecasting financial performance. The sentiment (tone, opinion) is assessed using several categorization schemes in order to explore various aspects of language used in the annual reports of U.S. companies. Further, we employ machine learning methods and neural networks to predict financial performance expressed in terms of the Z-score bankruptcy model. Eleven categories of sentiment (ranging from negative and positive to active and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 53 publications
(53 reference statements)
5
50
0
1
Order By: Relevance
“…However, the scope and structure of such information is different for well/poorly performing firms. Generally, the obtained results conform to the expectations of positive/negative sentiment categories (Davis et al, 2012;Hajek et al, 2014;Myskova & Hajek, 2016). The results of the present study suggest that firms that have good financial results verbally describe not only the achieved values of financial indicators, but they also elaborate the causes of the result in more detail.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…However, the scope and structure of such information is different for well/poorly performing firms. Generally, the obtained results conform to the expectations of positive/negative sentiment categories (Davis et al, 2012;Hajek et al, 2014;Myskova & Hajek, 2016). The results of the present study suggest that firms that have good financial results verbally describe not only the achieved values of financial indicators, but they also elaborate the causes of the result in more detail.…”
Section: Resultssupporting
confidence: 77%
“…Significant differences of word categories has been observed for firms with low/high earnings and stock returns (Li, 2008), stock market volatility (Loughran & McDonald, 2011), market-to-book ratio (Myskova & Hajek, 2016), return on assets (Davis et al, 2012), credit ratings (Hajek & Olej, 2013), Altman Z-score (Hajek et al, 2014). However, the dictionaries used previously are mostly limited with the focus on general linguistic categories, particularly on positive and negative sentiment.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…пример на рис. 1) неоднократно успешно использовалась для осуществле-ния текстового анализа, демонстрируя высокую достоверность полученных ре-зультатов, что также стало одним из осно-ваний для выбора данного типа модели [Savas et al, 2015;Hájek, Olej, Myskova, 2014].…”
Section: искусственные нейронные сетиunclassified
“…Their results show that adding sentiment information leads to a more accurate prediction of financial distress than when the prediction is based on financial information alone. In a subsequent research with more sentiment word categories Hajek et al (2014) showed that a change in the development of a company influences the textual sentiment information in the annual report.…”
Section: Financial Distressmentioning
confidence: 99%